Clinical application of polylactic acid/gelatin nanofibre membrane in hard-to-heal lower extremity venous ulcers. (2nd November 2022) - Chen, Hongrang; Shen, Yun; Zhang, Haitao; Long, Xiaoyan; Deng, Kunxue; Xu, Tao; Li, Yongsheng
Abstract : Objective: To evaluate the safety and effectiveness of polylactic acid/gelatin nanofibre membranes (PGNMs) in treating hard-to-heal lower extremity venous ulcer wounds. Method: In this prospective study, patients with venous leg ulcers (VLUs) were treated with PGNMs or standard of care. Wounds were assessed once a week until the wound was fully healed. Results: The treatment group was comprised of 10 patients with VLUs, aged between 47–64 years, with an average age of 56.58±6.19 years. The wounds were located in the lower leg and/or ankle. Average wound area was 8.91±13.57cm 2 (range: 1.5–52.5cm 2 ). Average wound healing time was 18.75±16.36 days. Of the patients, nine (90%) rated their pain as lighter when removing the dressing, with an average pain value of 2.0±1.0 points. There was less secondary trauma to the wound surface, and less bleeding. At six months after the wound healing, the scar evaluation (using the Vancouver Scar Scale) result was 3.75±1.96 points. Conclusion: In this study, the PGNMs were safe and effective in treating hard-to-heal lower extremity VLUs.